(3cJGH aj CfSGH GdeZQHs - (3CHh MjGfs
(3ChdgG (B:s
(3GYde Cf GdeZGQH YfO GdeDQNjf KdGKI s
(3BNQgG (B:s
(3djHMK GdHGMK dhdGOJge hhbJ haGJge heHdZ CYeGQge QVhGf Gddg Ydjge CLeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3HBNQg YOI fbhd eNJdaIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(1275(3c(B) s
Keywords: (3GdJGQjNs